Epigallocatechin gallate decorated carbon nanotube chemiresistors for ultrasensitive glucose detection - Salila Vijayalal Mohan, Hari Krishna (2018)
The concentration of glucose in biological fluids is in the micromolar range, the detection of which requires devices with high sensitivity and low limit of detection (LOD). Here, we report the real-time electronic detection of glucose using an antioxidant found in green tea, namely, epigallocatechin gallate (EGCG), decorated on carbon nanotubes (CNTs) and tested in a chemiresistor configuration. The detection principle relies on the spontaneous reaction of EGCG with hydrogen peroxide, a reactive oxygen species released during glucose oxidation, which is translated electrically as a change in CNT conductance. Our results suggest that the response of EGCG decorated CNTs was far superior to that of the bare CNT based device. The sensor detected glucose ranging from 10 nM to 1 μM with LOD of ∼8.7 nM, which is much lower than the commercially available finger-pricking based glucose sensors. This could pave the way for developing simple resistivity-based sensors capable of glucose detection in biological fluids other than blood, such as sweat and saliva.